Effects of human resource practices on turnover intention of multinational corporations: the mediating role of individualism/collectivism - Qin, Li; Mohamed, Rosmah; Mahomed, Anuar; Hanna Khan, . (Global Academic Excellence M Sdn Bhd, 2022)
The global gradual economic recovery has restored the voluntary turnover rate to the level before the outbreak of the epidemic. Cultural differences are considered to be an additional reason for the brain drain of foreign multinational enterprises. A survey was conducted to collect responses from 202 millennial in selected foreign multinational corporations in China. Therefore, the purpose of this study is to explore the relationship between human resource practice (HRPs) mediated by individualism/ collectivism (IC) and turnover intention (TI) by adopting the recognized and well-established social exchange theory, so as to provide new academic ideas for the Millennium employee management of multinational corporations in China. This study was utilized a cross-sectional study as a tools for data collection. For data analysis, this study implemented a Partial-Least Square (PLS) as tools of data analysis. The results highlight the mediating role of individualism/collectivism, reduce Millennium employee turnover intention. In addition, the results verify the negative effect of human resource practice on turnover intention. Therefore, it is important for the management of multinational enterprises in China to develop human resources practices that meet the cultural cognitive of Chinese employees. This study is the first to measure the mediating effect of individualism/collectivism, which defines the theoretical and practical significance and the direction of future research. In addition, more cultural factors will be added to the future research.